The determinants of job satisfaction in the Egyptian labor market - Asmaa Ezzat; Maye Ehab (Review of Economics and Political Science (REPS), 2019)
Purpose - This paper aims to analyze the determinants on job satisfaction in the Egyptian labor market, using Egypt's Labor Market Panel Survey (ELMPS), the wave of 2012. Design/methodology/approach - Several determinants are analyzed including the wage level, the paid and sick leaves, the medical and social insurance, job stability among other individual and job characteristics. To this end, an ordered logit model is estimated to assess the significance of these different variables as determinants for job satisfaction. Findings - The empirical findings indicate that wages and stability are major determinants for job satisfaction for the sample of wage workers. However, the results change according to gender; the hourly wage level affects men's level of job satisfaction, while it does not affect that of females. Furthermore, the job satisfaction of women is determined more by the job characteristics rather than the monetary compensation. Social implications - The empirical findings shed light on the importance of formalizing jobs, as it has an effect on the level of job satisfaction of both women and men. Originality/value - To the best of the authors' knowledge, this is the first paper to examine the determinants of job satisfaction for wage workers in Egypt using the ELMPS data.
Keywords: J0; J2; J3; 330; Job satisfaction; Egypt; Wages; Logit; Labor market